The Place of Qualitative Research in Public Health Dentistry - Barry Gibson, BSc, MMedSc, PhD (Blackwell Synergy, 2002)
The discussion between Siriphant (1) and Blinkhorn (2) is both exciting and interesting since it challenges us to consider the role and nature of qualitative research in dental public health. Such discussions are not new in dentistry and it seems that to some extent their character has maintained a familiar sensitive and combative tone. In particular, I am mindful of a similar discussion that occurred in the British Dental Journal in the late 1980s (3-8). In addition, discussions such as these have a surreal feel that (it never ceases to amaze) they should be necessary at all. The requirement that such debates need be repeated in much the same manner as they have previously has important implications for the type and quality of qualitative research that can and will be submitted to dental journals in the future. It is with this in mind that this commentary has been developed.